Vibrational spectra of two Fe(III)/EDTA complexes useful for iron supplementation - Wagner, Claudia Cecilia (2010)
The infrared and Raman spectra of Na[FeEDTA(H2O)]·2H2O and Na4[(FeEDTA)2O]·3H2O (EDTA = tetra anion of ethylenediaminetetraacetic acid), two complexes proposed as adequate for iron supplementation, were recorded and analyzed in relation to its structural peculiarities. Some comparisons between the recorded spectra are also presented, and the characteristics of the carboxylate motions as well as those of the metal-to-ligand vibrations are discussed in detail.